THE IMPLEMENTATION OF VILLAGE FUND POLICY IN IMPROVING ECONOMY OF VILLAGE SOCIETY - Ramly, Ar Royyan; Wahyuddin, Wahyuddin; Mursyida, Julli; Mawardati, Mawardati (SCAD Independent, 2018)
This study analyzed the implementation of the village budget allocation policy and the village fund allocation which became second source in village finance revenue. The analysis made is to see how this village fund policy is able to increase the economic potency of the village so that there is equal distribution of income in village society. The method used is qualitative with descriptive analysis approach. The results of this study indicated that the policy of village funds and the allocation of village funds in the case of Kuala Sub-district of Nagan Raya District still cannot increase the potential of the village through utilization village fund, while the potential of the village is very large. This is because the policy of village fund allocation is still directed to infrastructure development or physical potential, besides; there are still obstacles of human resources in managing the village funds. The village which is classified as independent is Simpang Peut village which manage their business through village business entity.